2001
DOI: 10.1017/s1355770x01000067
|View full text |Cite
|
Sign up to set email alerts
|

Water pollution abatement cost function: methodological issues and an application to small-scale factories in an industrial estate in India

Abstract: Formulation and estimation of a correctly specified abatement cost function would be central to policy formulation regarding imposing taxes or user-fees as well as of sharing social cost in the presence of environmental pollution. Often in research, the output of an abatement activity for water pollution appears to us not to have been clearly specified. This activity is very distinct from whatever is the actual product of the plant. We propose in this paper that the output is only and exclusively the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…It can also be seen from this table that abatement costs for a pollutant vary widely across different industries by a factor as much as 1 to 400. These estimates reaffirm the results of the earlier studies on abatement costs in India [Mehta, et al 1994;Pandey, 1999 and2000b;Goldar, et al 2001] which show large variations in abatement costs not only across the industrial sectors but also across firms within an industry. An important observation that can be made on the basis of these results is that the current legislation, which requires that all polluters meet the same discharge standards, is highly inefficient.…”
Section: Estimates Of the Ratio Of Cost Of Abatement Under Cac And Mbissupporting
confidence: 87%
“…It can also be seen from this table that abatement costs for a pollutant vary widely across different industries by a factor as much as 1 to 400. These estimates reaffirm the results of the earlier studies on abatement costs in India [Mehta, et al 1994;Pandey, 1999 and2000b;Goldar, et al 2001] which show large variations in abatement costs not only across the industrial sectors but also across firms within an industry. An important observation that can be made on the basis of these results is that the current legislation, which requires that all polluters meet the same discharge standards, is highly inefficient.…”
Section: Estimates Of the Ratio Of Cost Of Abatement Under Cac And Mbissupporting
confidence: 87%
“…One assumes that marketable output is separable from the production of pollutants (or pollution abatement). For example, Bellas (1998), Goldar et al (2001), and Dasgupta et al (2001) estimate marginal abatement costs assuming separability between marketable 2 Exceptions are FĂ©res and Reynaud (2005) and Pascoe et al (2007), who consider non-separability. FĂ©res and Reynaud (2005) investigate the water demand of Brazilian manufacturing by estimating a multiproduct translog cost function.…”
Section: Backgroundsmentioning
confidence: 99%
“…The results indicated that an overall betterment in environmental media is achievable through a combination of various instruments-standards, license fees, subsidies and charges-along with the necessary enforcement. Murty et al (2006) for sugar industry of India, Jiang and Mckibbin (2002) for China, Goldar et al (2001) for small factories in India, Dasgupta et al (2001) for some industries in China, Hailu and Veeman (2000) for Canadian pulp and study industry and Khalid (1996) for palm oil mills in Malaysia, Bataineh (2006) for improving of competition in manufacturing companies, Salleh et al (2007) for readiness in meeting globalization challenges, Nasir and Abdullah (2004) for accrual and cash flow measures investigated the effects of economic instruments on firm's environmental performance such as the level of pollution abatement.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%